1973
DOI: 10.1139/v73-198
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Related Compounds. 5. The Transformation of Formycin and Tubercidin into 2′- and 3′-Deoxynucleosides

Abstract: Reaction of tubercidin (4-amino-7-~-~-ribofuranosylpyrrolo[2,3-d]pyrimidine)(1) with a-acetoxyisobutyryl chloride in the presence of excess sodium iodide in acetonitrile gave an acylated iodo intermediate (2) which was converted into 3'-deoxytubercidin (4) by hydrogenolysis and subsequent saponification.Analogous treatment of formycin (7-amino-3-~-~-ribofuranosylpyrazo10[4,3-d]pyrimidine) (5) gave 3'-deoxyformycin (6) and 2'-deoxyformycin (7) in an approximate ratio of 3:2. These purified nucleosides, 6 and 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 10 publications
3
13
0
Order By: Relevance
“…The overall yield of 543 from 536 was 36%. The IH NMR spectrum of 543 was very similar to that reported (315,316) for 2'-deoxyformycin B (503) by Robins et al, but rather different from that reported by Rao et al (330) The H-I' signal of 543 at O 5.22 appeared as a double of doublet as that reported for 2'-deoxyformycin B (505), but not an apparent triplet as reported for 535. Deprotection of 543 by hydrogenolysis over palladium hydroxide (Degussa type) afforded 2'-deoxy-9-deazaadenosine, which also showed a double of doublet for H-I'.…”
Section: Modification Of the Sugar Without Base Participationsupporting
confidence: 77%
See 1 more Smart Citation
“…The overall yield of 543 from 536 was 36%. The IH NMR spectrum of 543 was very similar to that reported (315,316) for 2'-deoxyformycin B (503) by Robins et al, but rather different from that reported by Rao et al (330) The H-I' signal of 543 at O 5.22 appeared as a double of doublet as that reported for 2'-deoxyformycin B (505), but not an apparent triplet as reported for 535. Deprotection of 543 by hydrogenolysis over palladium hydroxide (Degussa type) afforded 2'-deoxy-9-deazaadenosine, which also showed a double of doublet for H-I'.…”
Section: Modification Of the Sugar Without Base Participationsupporting
confidence: 77%
“…(317) 2'-Deoxyformycin B (505) and 3'-deoxyformycin B (504) were prepared by deamination of 503 and 502, respectively, with calf intestinal deaminase. (316) When I{I-uridine was treated with 2-acetoxyisobutyryl chloride (267,318) in various solvents, a mixture of several compounds was obtained. These components were chromatographically separated and the two major products (after saponification) were identified as the 2'-chloro-ribosyl (508) and 3'-chloro-xylosyl (509) nucleosides, and two minor components as 2,4'-anhydro-(506) and 2'-chloro-arabinosyl nucleosides (507) (Scheme 45).…”
Section: Modification Of the Sugar Without Base Participationmentioning
confidence: 99%
“…In contrast to the corresponding reaction of the adenosine orthoester (9), no 2'-chloro isomers were detected. The absence of nucleophilic attack at the 2'-position of tubercidin has been noted previously in acetoxonium ion mediated reactions (5,6). The use of free radical dechlorination conditions (10) (tri-12-butyltin hydride plus a,al-azobisisobutyronitrile as initiator) with 3a followed by deblocking gave 3'-deoxytubercidin (8) (5,6) in 517, yield.…”
Section: Morris J Robins Roger a Jones Et Rudolf Mengel Can J Csupporting
confidence: 70%
“…The absence of nucleophilic attack at the 2'-position of tubercidin has been noted previously in acetoxonium ion mediated reactions (5,6). The use of free radical dechlorination conditions (10) (tri-12-butyltin hydride plus a,al-azobisisobutyronitrile as initiator) with 3a followed by deblocking gave 3'-deoxytubercidin (8) (5,6) in 517, yield. This allows use of the blocked chloro nucleosides for syntheses of specific deoxy derivatives whereas catalytic hydrogenolysis of chloro compounds has been generally unsuccessful (6,11).…”
Section: Morris J Robins Roger a Jones Et Rudolf Mengel Can J Csupporting
confidence: 70%
See 1 more Smart Citation